2017
DOI: 10.1038/srep44075
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of vascular endothelial growth factor receptors by tivozanib has potential anti-tumour effects on human glioblastoma cells

Abstract: Glioblastoma (GBM) remains one of the most fatal human malignancies due to its high angiogenic and infiltrative capacities. Even with optimal therapy including surgery, radiotherapy and temozolomide, it is essentially incurable. GBM is among the most neovascularised neoplasms and its malignant progression associates with striking neovascularisation, evidenced by vasoproliferation and endothelial cell hyperplasia. Targeting the pro-angiogenic pathways is therefore a promising anti-glioma strategy. Here we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 97 publications
(96 reference statements)
1
21
0
1
Order By: Relevance
“…GBM invasion. [19][20][21] In conclusion, our data demonstrated that treatment with foretinib leads to downregulation of MMP2 in GBM cell line and has a positive effect on T98 cells…”
Section: Discussionsupporting
confidence: 54%
“…GBM invasion. [19][20][21] In conclusion, our data demonstrated that treatment with foretinib leads to downregulation of MMP2 in GBM cell line and has a positive effect on T98 cells…”
Section: Discussionsupporting
confidence: 54%
“…Concomitantly, a remarkable downregulation of the expression levels of Cdc25C and Cyclin B1, key regulators involved in the G 2 /M cell cycle transition ( 37 , 38 ), was further observed in the treated cells compared with the control (untreated cells). A number of previous studies have demonstrated that in glioblastoma cell lines, downregulation of the expression levels of Cdc25C and Cyclin B1 has been implicated in the G 2 /M phase arrest induced by various antitumor agents, including arsenic trioxide ( 39 ), tivozanib, a pan-inhibitor of vascular endothelial growth factor ( 40 ), and knockdown of β-arrestin 1, a mediator of tachykinin receptor neurokinin-1 signaling pathway responsible for cell proliferation ( 41 ). Survivin, an important cancer-associated protein, is highly expressed in the majority of human tumor cells, including primary human glioblastoma cells ( 19 ), and its inhibition has been considered as a compelling strategy for cancer therapy ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The target gene expression levels were normalised to beta-2-microglobulin ( B2M ) levels in the same reaction. For calculations, 2 −ΔΔC T formula was used, with ΔΔC T  = (C T target − C T B2M ) experimental sample – (C T target − C T B2M ) control samples, where C T is cycle threshold 79 .…”
Section: Methodsmentioning
confidence: 99%